Marked olfactory impairment in idiopathic intracranial hypertension. Issue 9 (28th January 2014) - Bershad, Eric M; Urfy, Mian Z; Calvillo, Eusebia; Tang, Rosa; Cajavilca, Christian; Lee, Andrew G; Venkatasubba Rao, Chethan P; Suarez, Jose I; Chen, Denise
Abstract : Objective: Many long-duration astronauts develop signs of elevated intracranial pressure and have neuro-ophthalmological findings similar to idiopathic intracranial hypertension (IIH) patients. Some also present with nasal congestion and subjective olfactory impairment. We prospectively evaluated olfactory function in IIH patients and the effect of 6° head-down tilt, which simulates the headward fluid shifting in microgravity, as spaceflight analogues. Design: Olfaction was tested for all subjects in upright and 6° head-down tilt positions using two different measures: University of Pennsylvania Smell Identification Test and Olfactory Threshold Sniffin' Sticks with phenylethyl alcohol. Results: IIH patients (n=19) had significant impairment on both olfactory measures compared with matched controls (n=19). The olfactory threshold dilution levels were 9.07 (95% CI 1.85 to 5.81) and 3.83 (95% CI 7.04 to 11.10), p=0.001, and smell identification scores were 35.61 (95% CI 34.03 to 37.18) and 32.47 (95% CI 30.85 to 34.09), p=0.008, for control and IIH subjects, respectively. The threshold detection was mildly impaired in head-down tilt compared with upright position in the combined subjects (6.05 (95% CI 4.58 to 7.51) vs 6.85 (95% CI 5.43 to 8.27), p=0.004). Conclusions: We demonstrated that IIH patients have marked impairment in olfactory threshold levels, out of proportion to smell identification impairment. There was also impairment in olfactory threshold in head-down tilt compared with upright positioning, but not for smell identification. The underlying mechanisms for olfactory threshold dysfunction in IIH patients need further exploration.